잔탄검 첨가에 따른 어육단백질 스낵의 유지흡수율 및 품질 변화 - 정채영; 양지나; 오임경 (한국식품과학회지, 57(2), 2025)
With the growing demand for protein-rich foods, fish-protein snacks have gained attention due to their nutritional benefits. This study examined the effects of xanthan gum (XG) addition (0, 0.25, 0.50, and 0.75%) on the rheological, oil absorption, and sensory properties of fish protein snacks. The results showed that increasing the XG concentration led to a decrease in viscoelasticity and gel strength. The fat content was the highest in the control group and decreased by 10.3% with 0.75% XG. Additionally, oil absorption declined at higher XG levels. Microstructural analysis revealed that higher XG levels resulted in smaller pores and smoother surfaces. The snack with 0.50% XG had the crispiest texture in the texture analysis and had the highest overall acceptability in the sensory evaluation. In conclusion, xanthan gum effectively reduced oil absorption while enhancing the physical and sensory properties of fish protein snacks. KCI Citation Count: 0